Pencegahan Penyebaran Pandemi Covid-19 di Objek Wisata Cagar Budaya Kabupaten Gianyar, Bali - Zuraidah, Zuraidah; Sudana Wira Darma, I Kadek (Humanis; Vol 26 No 3 (2022)DO - 10.24843/JH.2022.v26.i03.p04, 2022)
The Covid-19 pandemic has drastically reduced tourism activity and has had an impact on the economy. To recover from this impact, with the new normal policy, the government will reopen tourism activities by implementing strict health protocols. This policy also applies in Gianyar Regency, Bali. This study aims to examine the prevention of the spread of the Covid-19 pandemic in the cultural heritage tourism sector in Gianyar Regency, Bali. The study applied qualitative methods which were analyzed descriptively. The results of the study indicate that the government has made policies regarding the application of health protocols in tourism activities. The protocols that have been implemented in cultural heritage tourism objects in Gianyar Regency include wearing masks, checking temperature, providing handwashing facilities, and holding supervision so that visitors always obey the health protocol. With the new normal policy, it is hoped that all people, especially those in the tourism sector, understand and implement better health protocols, to minimize the possibility of Covid-19 transmission in the tourism sector.